Design of Shared Appreciation Mortgage - Hu, Xiaoming (2006)
This dissertation integrates the mathematical design of an efficient risk-free traditional mortgage (Ebrahim 2006) with that of an Islamic convertible mortgage (Ebrahim and Khan 2002) to present a model of the shared appreciation mortgage. It is an innovative home mortgage product which allows prospective homeowners to borrow at a below-market contract rate, in exchange for this they have to pay the lender a predetermined percentage of future house price appreciation. The model is designed by considering the mortgage as a combination of a credit facility and an American call option.